In-depth Sampling Study of Charactersitics of Vehcile Crashes in Saudi Arabia - Al-Shammari, N. K.; Darwish, S. M. H. (Engineering, Technology & Applied Science Research, 2019)
It is imperative for any traffic safety enhancing effort to collate and analyze detailed data about crashes. This article describes a study that investigated all aspects related to motor vehicle crashes resulting in human injuries or deaths in Riyadh. The database consisted of 295 collisions involving 331 vehicles, 596 fatalities (car passengers and pedestrians) and 2,454 injuries with Abbreviated Injury Scale (AIS) ≥ 1. Results show that only 15.1% of all vehicle occupants were wearing seatbelts at the time of collision which is reflected in having most injuries occurring to upper parts of the body and the spine. It is also reflected in a high incidence rate of 0.22 fatalities per crash. The average age of victims was 33 years with three quarters of them being males. Results also show that human actions, like reckless driving, over speeding, and sudden lane deviations were the causes of most collisions. It is concluded that in order to improve traffic safety conditions in Riyadh and in the whole country, a change in driving culture of all road users is needed. This can only come with improved awareness of the risks involved among road users, better law enforcement and other engineering and hi-tech countermeasures like smart red lights.